2007
DOI: 10.1136/gut.2007.128694
|View full text |Cite
|
Sign up to set email alerts
|

Autologous haematopoietic stem cell transplantation without CD34+ cell selection in refractory Crohn's disease

Abstract: Autologous HSCT with unselected PBSC appears to be safe and can induce and maintain remission in previously refractory Crohn's disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(96 citation statements)
references
References 50 publications
0
88
0
8
Order By: Relevance
“…14,15 The authors report that 91% of patients achieved medication-free remission after 1 year, which lasted up to 5 years in selected patients. A similar rate of remission was observed in six patients transplanted in Milan 8,16 and in smaller series and independent case reports [reviewed in Refs. (9,17,18)].…”
mentioning
confidence: 51%
“…14,15 The authors report that 91% of patients achieved medication-free remission after 1 year, which lasted up to 5 years in selected patients. A similar rate of remission was observed in six patients transplanted in Milan 8,16 and in smaller series and independent case reports [reviewed in Refs. (9,17,18)].…”
mentioning
confidence: 51%
“…11,30 Therefore, these evidences suggest that SCT could be justified in some patients with IBD, which have already begun to be transplanted in some current trials, 42,43 thus raising the question of whether the cell transplantation or the intense immunosuppression was the critical event for patient recovery. In our study, both therapeutic approaches induced remission of the disease and, although we did not elucidate the exact mechanisms of action of the graft in the treatment of the IBD, we showed that in this model, the infusion of the graft was extremely important to reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
“…6 There has been considerable interest in case reports that autologous haematopoietic stem cell transplantation (HSCT) can induce sustained disease remission in such patients. [7][8][9][10][11][12][13] The ASTIC trial compared outcome at one year in 23 patients with refractory CD after autologous HSCT to 22 undergoing stem cell mobilisation alone. 14 This was a negative trial and few patients in either arm achieved the ambitious primary endpoint of clinical remission off therapy for 3 months with no endoscopic or radiological evidence of intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%